THE WOMEN’S SCIENCE: RELATIONS BETWEEN TEXT AND IMAGE IN THE UNESP CIENCIA MAGAZINE - Garrido, Bruno Sampaio (Laboratório Editorial FCL-UNESP, 2013)
This study aims at investigating the relations between verbal and nonverbal elements of a cover story of the Unesp Ciencia Magazine, and how they work in the construction of a global sense of the messages produced, so as to highlight the content addressed in the text, making it more attractive to readers. For the analysis, we chose the cover and the lead story for the 17th issue of the magazine, published in March 2011, addressing the plight of women scientists in occupying higher positions in the academic career. The corpus was analyzed in the light of French semiotics, in order to obtain a comprehensive understanding of constituent messages from studied elements and fundamental relations to the construction of meaning. As main results, it was verified that the theme portrayed in the object is articulated to grab the reader more easily for motivating him to continue the reading, drawing on elements pertaining to the cognitive-cultural average repertoire of audience, as portraying the inequality between men and women in academic career under the metaphor of a sports competition, among other figurativizations referring to the theme - like the fact that scientists accumulate social roles of professional, mother and home caretaker.